Navigating different public health roles in alcohol premises licensing: a multi-stakeholder interview study. (November 2021) - O'Donnell, Rachel; Mohan, Andrea; Purves, Richard; Maani, Nason; Egan, Matt; Fitzgerald, Niamh; ,
Abstract: Background: In England and Scotland, local governments regulate the sale of alcohol through premises licensing. In the past 10 years, some public health practitioner teams have become proactive in engaging with alcohol licensing to encourage actions regarded as likely to improve population health. These public health teams are largely based in the National Health Service in Scotland, and within local authorities in England. This research explored ways in which public health actors believe their activities make a difference to alcohol licensing decisions, policies, and systems, and the acceptability of their involvement from licensing stakeholder perspectives. Methods: All public health practitioner teams were directly informed about this multicentre study. Scoping calls were conducted with interested teams to explore their level of activity in alcohol licensing in 2012–19 across several pre-defined categories. Recruited local authority areas purposively varied by region and rurality. 53 in-depth telephone interviews (28 with public health actors and 25 with licensing stakeholders) were done in 20 local authority areas in England (n=14) and Scotland (n=6). Interview transcripts were analysed thematically with NVivo 12 using inductive and deductive approaches. Findings: Most public health actors felt that they could make a difference by broadening licensing decision makers' understanding of alcohol-related health harms. For many, a key motivation was to reduce harms through containing alcohol availability at current levels and, ultimately, long-term culture change. Others adapted their approach to fit with the aims of licensing staff, focusing on promoting responsible sale of alcohol, so-called responsible drinking, or both. In both cases, public health actors and licensing stakeholders viewed partnership working as key to effectiveness. Although most licensing staff valued public health involvement, a minority were sceptical about public health involvement focused on containing availability, considering this approach as too narrow in focus. Some public health actors felt unable to secure public health improvements within the constraints of current licensing systems, which have potential to prevent increases in alcohol availability but are unable to reduce alcohol availability. Interpretation: Public health actors take different approaches to engagement with alcohol licensing, including disruptive or collaborative approaches. Collaborative approaches were seen as more acceptable by some licensing stakeholders, but focus mainly on short-term outcomes other than health (eg, crime). The effectiveness of public health involvement, including through these different approaches, merits quantitative evaluation. Sampling did not include lower activity areas wherein experiences might differ. Funding: The ExILEnS study was funded by the National Institute for Health Research (project number 15/129/11). The views expressed in this work are those of the authors and do not necessarily reflect those of the National Health Service, the National Institute for Health Research, or the UK Government's Department of Health and Social Care.